Chemistry, mineralogy and microbiology of termite mound soil eaten by the chimpanzees of the Mahale Mountains, Western Tanzania - Mahaney, William C.; Wink, Michael (Journal of tropical ecology, 1999)
Subsamples of termite mound soil used by chimpanzees for geophagy, and topsoil never ingested by them, from the forest floor in the Mahale Mountains National Park, Tanzania, were analysed to determine the possible stimulus or stimuli for geophagy. The ingested samples have a dominant clay texture equivalent to a claystone, whereas the control samples are predominantly sandy clay loam or sandy loam, which indicates that particle size plays a significant role in soil selection for this behaviour. One potential function of the clays is to bind and adsorb toxins. Although both termite mound and control samples have similar alkaloid-binding capacities, they are in every case very high, with the majority of the samples being above 80%. The clay size material (< 2 μm) contains metahalloysite and halloysite, the latter a hydrated aluminosilicate (Al2Si2O4·nH<late x>$_2$</latex>O), present in the majority of both the termite mound soil and control soil samples. Metahalloysite, one of the principal ingredients found in the pharmaceutical KaopectateTM, is used to treat minor gastric ailments in humans. The soils commonly ingested could also function as antacids, as over half had pH values between 7.2 and 8.6. The mean concentrations of the majority of elements measured were greater in the termite mound soils than in the control soils. The termite mound soils had more filamentous bacteria, whereas the control soils contained greater numbers of unicellular bacteria and fungi.